Avaliação fitogeográfica dos relictos xerófitos em afloramentos rochosos no campestre do divino, Santa Maria/RS - Pontes, Rodrigo Corrêa (2017)
The present study aims to identify and evaluate the areas of ecological refuges with xerophytic species, present in the locality of Campestre do Divino, Santo Antão district, Santa Maria municipality, central region of the State of Rio Grande do Sul, southern Brazil, through an environmental analysis of botanical, climatic, geological and geomorphological aspects. The research was developed through field data collection. Atmospheric variables were obtained through reading instruments. Geomorphological observations were performed together with the survey of the xerophytic species considered relictual, relating their presence with the climate, geomorphology and geology of the study area. It was also sought to analyze the anthropic impacts when it was identified. With the data collected in the field, the areas of these xerophytic refuges were georeferenced and later thematic maps were elaborated for a better understanding of the geographic distribution. Based on the Pleistocene Refugia Theory and with data obtained in the field, an environmental analysis was carried out where it was possible to verify that the presence of these xerophytic elements present an intrinsic pedological relation, guaranteeing that the study area always contained an open phytophysiognomy. These islands of endemism are represented by relictual species belonging to the families Bromeliaceae, Cactaceae and Orchidaceae, bioindicators of paleoclimatic events of intense aridity established in the Quaternary. Sheltered in rocky outcrops and litholic neosols, these endemic and endangered floristic elements, have maintained their survival processes, lingering in our landscape in adverse climatic conditions.